Living well under the shade of the new normal - Lamberte, Mario B.; Aldaba, Fernando T.; Brillantes, Alex B., Jr; Basilio, Enrico L.
The book analyzes comprehensively the COVID-19 impacts on the Philippines' economy and the effectiveness of the monetary and fiscal policies in response to the pandemic shock. It also provides a forward-looking policy framework for the Philippines' economy to regain the growth momentum. It is an excellent reference book for policy makers of developing countries to learn how to cope with similar shocks in the future.